Risk factors of perceived stigma in leprosy affected and non-affected persons in Non Somboon, Khon Khaen Province, Thailand - Nils Kaehler (Chulalongkorn University, 2013)
Thesis (M.P.H.)--Chulalongkorn University, 2012